HOW DOES EU MEMBERSHIP AFFECT NON-FINANCIAL REPORTING? EVIDENCE FROM SELECTED BALKAN COUNTRIES - Tocev, Todor; Malchev, Bojan; Trpeska, Marina; Minovski, Zoran (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
Non-financial reporting is a form of transparency disclosure where companies disclose information that is not primarily focused on their financial performance, but information related to their activities that contribute to society through environmental protection, social matters, employees, human rights, anti-corruption and other activities affecting the supply chain. The purpose of this research is to analyze non-financial disclosure in selected Balkan countries and to determine how EU membership affects the scope of non-financial reporting. Four countries are included in the research, two of which are EU countries and two are non-EU countries. A total of 40 blue-chip companies that are part of the national stock market indexes for the period of 2019 to 2021 were taken as a sample in the research. We applied content analysis to 120 Audited Consolidated Annual Reports, individual Non-financial Disclosure Reports and all tabs and sub-tabs of official websites from which we identified variables to be statistically tested. A detailed descriptive and comparative analysis will be made to qualitatively and quantitatively describe the characteristics of non-financial reporting in the respective countries, and then the Multivariate Kruskal-Wallis will be conducted to test whether EU membership affects the extent, title, type, and length of the report on non-financial information.
Keywords: Non-financial reporting, EU membership, Balkan countries